Conjugate heat and mass transfer on fluctuating mixed convection flow along a vertical wedge with thermal radiation - Hossain, Anwar; Roy, Nepal; Firoza, M.N. (Zielona Góra: Uniwersytet Zielonogórski)
We study the boundary layer characteristics of heat and mass transfer flow past a vertical wedge in the presence of thermal radiation. The surface temperature and the species concentration are assumed to be oscillating in the magnitude but not in the direction of oncoming flow velocity. The governing equations have been solved by two distinct methods, namely, the straightforward finite difference method for the entire frequency range, and the series solution for the low frequency range and the asymptotic series expansion method for the high frequency range.
Keywords: mixed convection; thermal radiation; vertical wedge